Visible Proofs of Valour: The Trophy in South Italic Iconography of the Fourth Century BC - Michael Burns (Papers from the Institute of Archaeology, 2003)
In the regions of southern Italy known to the Romans as Campania and Lucania, there are numerous tomb and vase paintings of warriors from the fourth century BC. A recurrent theme in these paintings is ‘the return of the warrior’, in which a warrior, who is often mounted, arrives home carrying a trophy of spoils stripped from defeated enemies over his shoulder. The image of the victorious warrior in these scenes has often been interpreted as an idealistic image created to flatter the martial pretences of the aristocracy and not a reality of warfare. This paper discusses the ideology behind the iconography of the trophy and attempts to understand the heroic ethos of the south Italic warrior. Using evidence from literary and archaeological sources, this study concludes that the heroic iconography was far from being just an ideal of the elite. Spoils taken from enemies were seen as visible proofs of a warrior’s prowess and valour in battle, and were a way in which even the most humble warrior could acquire prestige and honour in south Italic society.
Keywords: Warfare; Italy; Iconography